Penggunaa APLIKASI TRACKER PADA MATERI KINEMATIKA - Siregar, Yenni Amalia (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research is to determine students' physics learning outcomes by using a tracker application on kinematics material. Where the use of the tracker application is assessed through tests that are integrated with the tracker. This research aims to see the effect of using a tracker application as a learning medium in stimulating students regarding graphs of the relationship between physical quantities and motion. Thus, using a tracker can increase students' understanding in interpreting graphs of the relationship between physical quantities and kinematics. Increasing students' understanding of graphs causes an increase in students' physics learning outcomes. The data shows that the final average of the control class is 55.0 while the final average of the experimental class is 62.3. From the final average score of the two classes, it can be seen that the final score for the experimental class is higher than the control class. Based on these data, it can be concluded that the use of the tracker application can improve students' physics learning outcomes.